A Novel Combination of Genes Causing Temperature-Sensitive Hybrid Weakness in Rice - Than Kutay Soe,; Kunieda, Mai; Sunohara, Hidehiko; Inukai, Yoshiaki; Reyes, Vincent Pamugas; Nishiuchi, Shunsaku; Doi, Kazuyuki (Frontiers in Plant Science, 2022)
Reproductive isolation is an obstacle for plant breeding when a distant cross is demanded. It can be divided into two main types based on different growth stages: prezygotic isolation and postzygotic isolation. The hybrid weakness, which is a type of postzygotic isolation, can become a problem in crop breeding. In order to overcome reproductive isolation, it is necessary to elucidate its mechanism. In this study, genetic analysis for low temperature-dependent hybrid weakness was conducted in a rice F2 population derived from Taichung 65 (T65, Japonica) and Lijiangxintuanheigu (LTH, Japonica). The weak and severe weak plants in F2 showed shorter culm length, late heading, reduced panicle number, decreased grain numbers per panicle, and impaired root development in the field. Our result also showed that hybrid weakness was affected by temperature. It was observed that 24°C enhanced hybrid weakness, whereas 34°C showed recovery from hybrid weakness. In terms of the morphology of embryos, no difference was observed. Therefore, hybrid weakness affects postembryonic development and is independent of embryogenesis. The genotypes of 126 F2 plants were determined through genotyping-by-sequencing and a linkage map consisting of 862 single nucleotide polymorphism markers was obtained. Two major quantitative trait loci (QTLs) were detected on chromosomes 1 [hybrid weakness j 1 (hwj1)] and 11 [hybrid weakness j 2 (hwj2)]. Further genotyping indicated that the hybrid weakness was due to an incompatible interaction between the T65 allele of hwj1 and the LTH allele of hwj2. A large F2 populations consisting of 5,722 plants were used for fine mapping of hwj1 and hwj2. The two loci, hwj1 and hwj2, were mapped in regions of 65-kb on chromosome 1 and 145-kb on chromosome 11, respectively. For hwj1, the 65-kb region contained 11 predicted genes, while in the hwj2 region, 22 predicted genes were identified, two of which are disease resistance-related genes. The identified genes along these regions serve as preliminary information on the molecular networks associated with hybrid weakness in rice.